Analysis of the immune status from peripheral whole blood with a single-tube multicolor flow cytometry assay - Donaubauer, Anna-Jasmina; Becker, Ina; Rühle, Paul-Friedrich; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Methods in Enzymology, 2020)
Supplementation of standard cancer therapies (radiotherapy, chemotherapy, surgery) with immunotherapies has revolutionized cancer treatment. In order to include recent improvements of multimodal therapies into clinical routine, knowledge about the immune status, the immune dynamics and the detailed composition and activation of patient's immune system is required. The here presented single-tube multicolor flow cytometry assay allows the discrimination of 20 clinically relevant immune cell subsets and their activation status in peripheral whole blood. It includes 15 different antibodies and can be established on a common 3 laser and 10 color flow-cytometer. Furthermore, this assay is easy to set-up and to perform as well as fast with only 40 min of sample preparation time. Moreover, only 100 μL of whole blood are sufficient for this precise determination of the individual immune status. It is already applied in translational programs of clinical studies and trials and can further be adapted for future ones.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Immune status; Immunophenotyping; Multicolor flow-cytometry; Peripheral whole blood; Radioimmunotherapies